A nonlocal boundary value problem for semilinear leveling of mixed type (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
This article presents the formulation of some mixed problems for an equation of the third-order composite type. Under certain conditions, the correctness of these problems in S. L. Sobolev spaces is proved for the coefficients and the right-hand side of the equation. Keywords: mixed boundary value problems, equations of composite type, theorem, cylindrical domain, regular problems, differential equation, S.L. Sobolev spaces, Green's formula